Effect of the use of Cajanus cajan (pigeon pea) meal on productive indicators of quails - Toro, Blanca; Cepeda, Mercedes; Chacón, E.; Sambache, J. E.; Martínez, Maira; Bastidas, H. P.; Brito, G. G.; Calderón, Cristina; Silva, Lucía M. (Cuban Journal of Agricultural Science, 2020)
To evaluate the effect of the use of Cajanus cajan (pigeon pea) meal on production indicators of quail, an amount of 160 quails was used, with 43 days old and an average weight of 149 ± 0.25 g, distributed in a completely randomized design with four treatments, four repetitions (40) and 10 animals per repetitions. Dry matter, crude protein, ashes, crude fiber and ether extract were determined, as well as metabolizable energy. Indicators initial and final weight, daily mean weight gain, food conversion, laying index, viability, shell thickness, white and yolk height, and shape index were evaluated. The best results were obtained in control treatment, and when including 10 % of meal with 18.19 %, 0.34 g and 0.21 g for laying index, egg weight and mean daily weight gain, respectively. Laying index showed the highest values for control, 10 % of pigeon pea meal has a chemical and amino acid composition suitable for its use in animal feed. Up to 10% of seed meal can be included in quail feed, without affecting the main productive and quality indicators of the egg. Key words: meal, Cajanus cajan, quail, production, egg quality